Secular trends and features of thalamic hemorrhages compared with other hypertensive intracerebral hemorrhages: an 18-year single-center retrospective assessment - Katano, Hiroyuki; Nishikawa, Yusuke; Uchida, Mitsuru; Yamanaka, Tomoyasu; Hayashi, Yuki; Yamada, Shigeki; Tanikawa, Motoki; Yamada, Kazuo; Mase, Mitsuhito (Frontiers in Neurology, 2023)
Trends regarding the locations of hypertensive cerebral hemorrhages are unclear. To clarify hypertensive hemorrhage trends, we investigated intracerebral hemorrhages (ICHs) over an 18-year period, focusing on thalamic hemorrhages compared with other sites of hemorrhages.We reviewed the cases of patients hospitalized for hypertensive ICH in 2004-2021 at our hospital; 1,320 eligible patients were registered with a primary ICH/intraventricular hemorrhage. After exclusion criteria were applied, we retrospectively analyzed 1,026 hypertensive ICH cases.The proportions of thalamic and subcortical hemorrhages increased over the 18-year period, whereas putaminal hemorrhage decreased. Multivariate logistic regression analyses revealed that for thalamic hemorrhage, ≥200 mmHg systolic blood pressure (p=0.031), bleeding <15 mL (p=0.001), and higher modified Rankin scale (mRS) score ≥4 at discharge (p=0.006) were significant variables in the late period (2013-2021) versus the early period (2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012), whereas for putaminal hemorrhage, significant factors in the late period were triglyceride <150 mg/dL (p=0.006) and mRS score ≥4 at discharge (p=0.002). Among the features of the thalamic hemorrhages in the late period revealed by our group comparison with the putaminal and subcortical